A3_9 All I Want Thaw Christmas Is You - Holland, Katie; Flood, Laura; Leversha, Thomas; Manley, Max (Physics Special Topics, 2022)
In this paper, we investigate if it would be possible to defrost Mariah Carey from an ice cube of length 2 m in time for the 1st of December if you began defrosting her on the 1st of November. It was found that it would take a total of 12.6 days for Mariah to return to normal body temperature, leaving her plenty of time to prepare for the Christmas season before it arrives.